THE SELLER’S LIABILITY DUE HIDDEN DEFECTIVE PRODUCTS IN THE ONLINE SELLING AND BUYING TRANSACTION BASE ON UUPK - Sujono, Imam; Mangesti, Yovita Arie; Suhartono, Slamet (International Journal of Law Reconstruction, 2022)
The seller offers goods with online media by relying on the description of the goods in the form of videos or photos so that consumers cannot directly check the goods to be purchased. This article analyzes the seller's liability due to hidden defects in online buying and selling transactions. This study uses a normative juridical approach. Results of the study show that hidden defective products sold by sellers in online transactions are the absolute responsibility of the seller as regulated in Article 19 of the UUPK, as well as the provisions of Articles 1365 and 1865 of the Civil Code, namely the seller is responsible for the goods sold. However, this responsibility must be proven that the seller did make a mistake, and the result of the mistake has been detrimental to the consumer. Besides the obligation of consumers to be careful, consumers also need to get protection.